A practical guide to the management of immune thrombocytopenia co-existing with acute coronary syndrome - Rahhal, Alaa; Provan, Drew; Ghanima, Waleed; González-López, Tomás José; Shunnar, Khaled; Najim, Mostafa; Ahmed, Ashraf Omer; Rozi, Waail; Arabi, Abdulrahman; Yassin, Mohamed (Frontiers in Medicine, 2024)
Introduction Immune thrombocytopenia (ITP) management with co-existing acute coronary syndrome (ACS) remains challenging as it requires a clinically relevant balance between the risk and outcomes of thrombosis and the risk of bleeding. However, the literature evaluating the treatment approaches in this high-risk population is scarce. Methods and Results In this review, we aimed to summarize the available literature on the safety of ITP first- and second-line therapies to provide a practical guide on the management of ITP co-existing with ACS. We recommend holding antithrombotic therapy, including antiplatelet agents and anticoagulation, in severe thrombocytopenia with a platelet count < 30 × 109/L and using a single antiplatelet agent when the platelet count falls between 30 and 50 × 109/L. We provide a stepwise approach according to platelet count and response to initial therapy, starting with corticosteroids, with or without intravenous immunoglobulin (IVIG) with a dose limit of 35 g, followed by thrombopoietin receptor agonists (TPO-RAs) to a target platelet count of 200 × 109/L and then rituximab. Conclusion Our review may serve as a practical guide for clinicians in the management of ITP co-existing with ACS.